Development of Control and Monitoring of BLDC Motor Speed without Sensor with Back Emf Detection - Nada Syadza Azizah; Feri Adriyanto; Joko Slamet Saputro (Universitas Sebelas Maret (UNS), 2023)
The development of technology at this time has an important role for all human needs and needs. One of the technologies that are currently developing is technology in the field of transportation. The development of electric vehicles is very relevant to be developed. However, in electric vehicles on the market, the control system used is less than optimal to respond to the load given to electric vehicles, resulting in a decrease in performance and waste of electrical energy. In general, BLDC motors which are often used as control systems use a position sensor (Hall effect sensor) in determining driver commutation. The use of position sensors often results in errors in configuration with the controller, difficulty in installation in case of damage, sensitivity of the sensor to temperature increases and the price of the sensor is relatively expensive. The use of sensorless method with Back EMF detection is an alternative solution to determine inverter commutation on BLDC motors. In this thesis, a BLDC motor speed control is developed which provides optimal, efficient and safe performance. This control system uses driver IC IR2101 and power switching MOSFET IRFZ44N. As a prototype, a 1000KV BLDC motor is used, controlled by an Arduino microcontroller and an ESP32 which is monitored by Blynk. The result achieved is that this system is able to control the rotation of the motor and stabilize the speed when there is a change in load. The efficiency of the no-load system reaches 46.48% and at maximum loading it reaches 36.98%, the best efficiency is obtained in the propeller II loading variation with an efficiency of 86.34%.